2013
DOI: 10.1098/rsbl.2012.1000
|View full text |Cite
|
Sign up to set email alerts
|

Rat aversion to isoflurane versus carbon dioxide

Abstract: Some experts suggest that sedation of laboratory rodents with isoflurane before euthanasia with carbon dioxide (CO 2 ) is a humane alternative to euthanasia with CO 2 alone, but little research has compared aversion with these agents. Albino rats were tested in a light -dark box where they had the choice between remaining in a dark compartment filling with isoflurane or CO 2 , or escaping to a lit compartment. Experiment 1 validated the procedure by confirming that rats responded to agent and light intensity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(90 citation statements)
references
References 16 publications
(14 reference statements)
3
83
1
1
Order By: Relevance
“…In addition, a series of studies have now shown that rodents do not willingly tolerate exposure to similar CO 2 concentrations. [15][16][17][18][19][20][21] Therefore, if CO 2 is used to kill rodents, refinements to minimize distress during this procedure are important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a series of studies have now shown that rodents do not willingly tolerate exposure to similar CO 2 concentrations. [15][16][17][18][19][20][21] Therefore, if CO 2 is used to kill rodents, refinements to minimize distress during this procedure are important.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 In the veterinary literature, dyspnea typically refers to labored breathing in animals, as currently labored breathing is associated with a negative affective experience in mice or rats. However, previous studies in mice and rats have shown that CO 2 concentrations ranging from 3-20% are aversive, [15][16][17][18][19][20][21] concentrations between 10 and 35% have been shown to cause fear responses, [22][23][24] and 10% CO 2 may be used as an 24 In the current study, labored breathing was directly assessed but we cannot be certain that this behavior was associated with a negative affect. However, on the basis of human evidence and the rodent research on aversion and fear responses, we posit that this autonomic response is accompanied by a negative affective experience.…”
mentioning
confidence: 99%
“…Unfortunately both objectively assessing animal welfare and non-invasively measuring disease progression are challenging and can therefore be obstacles to refining disease studies involving mice. Imaging is often advocated as a minimally invasive method of tracking disease progression (Hudson, 2005; Committee on Recognition and Alleviation of Distress in Laboratory Animals, 2008), but anaesthesia is typically required which may affect experimental outcomes and have a welfare cost (Wong et al, 2013). Identifying further behavioural biomarkers of disease progression through cooperation between biomedical scientists and ethologists (Broom, 2006) could therefore help to refine disease studies involving mice.…”
Section: Introductionmentioning
confidence: 98%
“…While immersion in "pre-filled" chambers had the advantage of rapid onset of unconsciousness and time to death, it has been demonstrated that exposure to high concentrations of gas leads to the formation of carbonic acid on the mucous membranes, leading to discomfort in humans at concentrations of 30% and pain at higher concentrations. Unfortunately, even with slow filling it is apparent that rodents are able to detect, and actively avoid, concentrations of CO2 well below the anesthetic threshold Wong et al, 2012). this is not entirely surprising given their evolution as a burrow living species, and has spawned any number of attempts to find a cheap, safe, inhaled agent that would be more humane.…”
Section: Euthanasia Of Rodents Is Still In Need Of Refinementmentioning
confidence: 99%
“…the most recent evidence would appear to suggest that inhaled anesthetic agents would be preferable, as rats given the choice between anesthetic concentrations of isoflurane and a bright light very often chose to remain in the gas to the point of unconsciousness. However, even this work is not without caveats, as the same animals quickly fled the gas on a second exposure, suggesting that isoflurane euthanasia would be a more humane alternative to CO2 only in cases where the animals had not previously been exposed to it during surgery or other procedures (Wong et al, 2012).…”
Section: Euthanasia Of Rodents Is Still In Need Of Refinementmentioning
confidence: 99%